Allergy, Serum IgE, and Lung Function in Children and Adolescents With Severe or Difficult-to-Treat Asthma - Haselkorn, T.; Szefler, S.J.; Simons, F.E.R.; Mink, D.R.; Chipps, B.E.; Wong, D.A.; Borish, L. (Journal of allergy and clinical immunology, 2007)
The chi-square test for categorical variables and ANOVA for continuous variables were used to identify significant differences in allergic measures among age groups, stratified by gender.